Forme galeniche e qualità di vita: il caso di tramadolo - Zaniolo, Orietta (Farmeconomia. Health Economics and Therapeutic Pathways, 2005)
Tramadol is a weak opioid analgesic used for moderate to severe pain control in acute and chronic diseases. Two new formulations of tramadol are recently admitted for marketing: once-daily (OD) controlled-release and fast-release orodispersible tablets. OD tramadol with its special lipophilic matrix permits to prolong drug effect up to 24 hours with a steady-state bioavailability comparable to that of immediate-release formulations. The efficacy and safety of this formulation of tramadol was evaluated in several trials on patients with moderate to severe chronic pain from osteoarthritis. These studies show similar effect of OD tramadol compared to standard formulation in pain control, quality of sleep, physical and mental functions, dropouts due to insufficient therapeutic effect and adverse events. Specially in the elderly and in chronic pain patients, frequency and complexity of dosing regimen remarkably affects quality of life. Furthermore, several studies show that a high number of daily administrations is one of the main factors that reduce patient compliance. For these reasons, OD tablets of tramadol seem to improve quality of life and acceptability of the therapy. Tramadol orodispersible tablets are useful for acute pain control, in the titration phase and for breakthrough pain control in chronic diseases. The manifacturing process of this formulation allows for rapid disintegration (20-30 seconds), once placed into the mouth, secondary to contact with salivary enzymes. This property facilitates its administration (in every place, without need of water), primarily for people with difficulty in swallowing tablets. Furthermore, respect to drops, it decreases the risk of misdosage. A open, randomized crossover study shows that, even although the galenics of tramadol in orodispersible and conventional fast-release capsules are different, they are bioequivalent and have similar pharmacokinetic parameters.